Molecular properties of uterine cytosolic and nuclear oestrogen and progesterone receptors of the primate cercopithecus aethiops pygerythrus. - Klien, Tirza (My University, 1985)
In the past 25 years, a large volume of data was collected on steroid hormone receptors and their role in the action mechanisms of steroid hormones. Efforts were made to use the principles, derived from fundamental investigations into the actual function of steroid hormone receptors in target tissues, (e.g. breast and uterine tissues) to provide a comprehensive understanding of the nature of hormone responsive tumours (e.g. breast tumours) and to formulate successful endocrine treatment regimes for e.g. breast cancer patients. Although some measure of success was achieved with antihormonal drugs like tamoxifen, clomiphene, medroxyprogesterone acetate, etc. a statistical analysis of patient response data has revealed disappointingly low median response times for breast cancer patients. A number of reasons can be offered in explanation of the discrepancies between theory and practice, however, it was felt that the two most obvious ones are the lack of a proper animal model, closer to man on the species scale, and insufficient understanding of the actual in vivo mechanisms of steroid hormone action. For this very reason it was decided to launch an in depth investigation into the properties and functions of steroid hormone receptors in the biological action of steroid hormones, especially the sex steroid hormone receptors, like the oestrogen and progesterone receptors. Furthermore, it was decided to employ a nonhuman primate, Cercopithecus aethiops pygerythrus, commonly called the Vervet monkey, as the animal model, instead of the more common Sprague-Dawley rat. Since the field of investigation defined is both broad and deep, it is obvious that this thesis could not contain all the answers. So, in view of the obvious limitation in time and man-power, the prime object for this thesis was defined as the laying of sound foundations for future research on the topic specified above. Thus, it was decided to concentrate on the molecular properties of the uterine oestrogen and progesterone receptors of the Vervet monkey. The basic arsenal of biochemical technology used in protein chemistry (competitive protein binding assays, sucrose density gradient analysis, size exclusion chromatography, ion exchange chromatography, chromatofocussing, isoelectric focussing) and available in the Institute of Life Sciences, Faculty of Medicine, University of Pretoria at the time of this investigation, was employed. In view of the information generated in the course of the study, attention was focussed upon a small, but important aspect of the mechanism of steroid hormone action, namely the process of activation or tranformation of receptor- ligand complexes and their interaction with the nuclear compartment. Since disturbance(s) in these processes in abnormal uterine tissues may exist, a limited study of the oestrogen and progesterone receptors in human uterine tissues was undertaken, because no abnormal Vervet monkey uterine tissues were available. Unfortunately it was also extremely difficult to obtain an abundance of pathological human uterine tissues necessary for an adequate study. The investigator consequently had to be content to study only a small number of pathological uterine specimens. Thus the latter part of this thesis only skims the surface of what could have been a major fait accompli with possible clinical significance.
A thesis submitted to the Faculty of Medicine University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy.
Keywords: Receptors, Progesterone; Receptors, Estrogen; Cercopithecus aethiops